Taxonomic review of the Afrotropical genus Birketsmithiola Krüger with descriptions of five new species (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V. (Zootaxa, 2022)
The footman moth genus Birketsmithiola Krüger, 2015 is reviewed and five new species are described: B. kruegeri sp. n. (eastern D.R. Congo), B. kingstoni sp. n. (Malawi), B. smithi sp. n. (Zambia and Malawi), B. nakuru sp. n. (Kenya), and B. bvumba sp. n. (Zimbabwe). Eilema sanguicosta var. nyassana Strand, 1912 previously considered as an unavailable name is restored and upgraded to species level: B. nyassana (Strand, 1912), stat. rev. Lectotypes for Ilema sanguicosta Hampson, 1901 and Eilema sanguicosta var. nyassana Strand, 1912 are designated. Adults together with male and female genitalia of all Birketsmithiola species are illustrated.